2022
DOI: 10.1007/s10840-022-01279-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pulmonary vein variant anatomy and cross-sectional orifice area on freedom from atrial fibrillation recurrence after cryothermal single-shot guided pulmonary vein isolation

Abstract: Background Cryoballoon (CB)-guided pulmonary vein isolation (PVI) is an established treatment for atrial fibrillation (AF). This study aimed to evaluate ablation efficacy and freedom from arrhythmia recurrence using the novel POLARx compared to the Arctic Front Advance Pro (AFA) CB system including the analysis of individual PV characteristics. Methods A total of 687 patients underwent CB-guided ablation for AF. Arrhythmia recurrence was defined as an ECG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 29 publications
4
11
0
Order By: Relevance
“…1,4,5 Several studies point out the importance of LGE CMR imaging for the visualization of individual atrial fibrosis prior to the ablation procedure. [4][5][6][7] In our study, LGE CMR revealed an intermediate amount of 21.41% ± 6.32% of LA fibrosis consistent with Utah stages II-III. Importantly, no PERS AF patient was assigned to Utah stage I as all patients had more than 10% fibrosis of the LA.…”
Section: Lge Cmr Imaging In Pers Afsupporting
confidence: 66%
“…1,4,5 Several studies point out the importance of LGE CMR imaging for the visualization of individual atrial fibrosis prior to the ablation procedure. [4][5][6][7] In our study, LGE CMR revealed an intermediate amount of 21.41% ± 6.32% of LA fibrosis consistent with Utah stages II-III. Importantly, no PERS AF patient was assigned to Utah stage I as all patients had more than 10% fibrosis of the LA.…”
Section: Lge Cmr Imaging In Pers Afsupporting
confidence: 66%
“…Recent studies have associated POLARx with shorter time to balloon temperature − 30 °C (T‐30), lower balloon nadir temperatures (NT), and longer balloon thawing time till 0 °C (TT0); however, time to isolation (TTI) was similar to AFAP 5,6 . Furthermore, POLARx appeared to be safe, efficacious, and demonstrated a comparable 1‐year outcome 7–10 . Biophysical parameters such as balloon NT and TT0 have been associated with durability of PVI after CB ablation 11–13 .…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary vein (PV) anatomy can affect cooling kinetics and CB ablation outcome 14–17 . A recent study demonstrated an association between cross‐sectional orifice area of the superior PVs and outcome after CB ablation in patients with paroxysmal AF 9 . Normal PV anatomy was associated with a significantly improved outcome for both catheter systems 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persistence of the SPV presenting as a separate atretic chamber and lacking any connection with atrium has been reported as a very rare condition that requires immediate recognition and surgical intervention [13]. Knowing about the incidence and tracing the origin of these anomalous veins has great clinical relevance as it could be misread as an arteriovenous malformation or could be life threatening if noticed only intraoperatively [14].…”
Section: Discussionmentioning
confidence: 99%